Lay Stakeholders in Science and Research Initiative: A Science Advisory From the American Heart Association. Issue 5 (3rd August 2021) - Roach, William H.; Bischoff, James M.; Dennis, Bernie; Donalson, Marvis; Dunbar, Sandra B.; Hill, Debbie; Ng-Osorio, Jacqueline; Powers, Sally; Wold, Loren E.
Abstract : The American Heart Association (AHA) is the largest not-for-profit funder of cardiovascular and cerebrovascular disease research in the United States. It has supported research of independent scientists for 7 decades with the goal of finding novel discoveries that will reduce death and disability from these diseases and ultimately improve overall health. In 2014, the AHA approved a pilot initiative to include lay stakeholders (patients, caregivers, and passionate advocates) in its research and science operations. The initiative was based on the premise that lay stakeholders would add a unique and necessary perspective that would improve decisions concerning research funding, research direction, and scientific guidelines. The AHA developed a framework for the initiative that defined lay stakeholder, created a volunteer recruitment and training program, established policies for incorporating lay stakeholders into science operations, and set metrics for evaluating the initiative over time. It has instituted creative ways to engage lay volunteers and to foster lay and scientist cooperation. Program assessments have been consistently positive and have identified needed future improvements. The benefits of lay/scientist collaboration have far exceeded the AHA's expectations. The AHA will continue to strengthen lay volunteer engagement throughout its science and research operations; to focus on developing a larger, diverse group of qualified lay stakeholders; to educate scientists on how to communicate research effectively to the public and donors; and to retain the respect of donors for the rigors of its research funding, scientific statements, and clinical guidelines.